Pluto's ephemeris from ground-based stellar occultations (1988-2016) - Desmars, J.; Meza, E.; Sicardy, B.; Assafin, M.; Camargo, J. I.B.; Braga-Ribas, F.; Benedetti-Rossi, G.; Dias-Oliveira, A.; Morgado, B.; Gomes-Júnior, A. R. [UNESP]; Vieira-Martins, R.; Behrend, R.; et al. (EDP Sciences, 2019)
Context. From 1988 to 2016, several stellar occultations have been observed to characterise Pluto's atmosphere and its evolution. From each stellar occultation, an accurate astrometric position of Pluto at the observation epoch is derived. These positions mainly depend on the position of the occulted star and the precision of the timing. Aims. We present 19 Pluto's astrometric positions derived from occultations from 1988 to 2016. Using Gaia DR2 for the positions of the occulted stars, the accuracy of these positions is estimated at 2-10 mas, depending on the observation circumstances. From these astrometric positions, we derive an updated ephemeris of Pluto's system barycentre using the NIMA code. Methods. The astrometric positions were derived by fitting the light curves of the occultation by a model of Pluto's atmosphere. The fits provide the observed position of the centre for a reference star position. In most cases other publications provided the circumstances of the occultation such as the coordinates of the stations, timing, and impact parameter, i.e. the closest distance between the station and centre of the shadow. From these parameters, we used a procedure based on the Bessel method to derive an astrometric position. Results. We derive accurate Pluto's astrometric positions from 1988 to 2016. These positions are used to refine the orbit of Pluto'system barycentre providing an ephemeris, accurate to the milliarcsecond level, over the period 2000-2020, allowing for better predictions for future stellar occultations.
Keywords: Astrometry; Celestial mechanics; Ephemerides; Kuiper belt objects: Individual: Pluto; Occultations